1998
DOI: 10.1088/1126-6708/1998/04/003
|View full text |Cite
|
Sign up to set email alerts
|

Quark Number Fractionalization in N = 2 Supersymmetric SU(2) × U(1)Nf Gauge Theories

Abstract: Physical quark-number charges of dyons are determined, via a formula which generalizes that of Witten for the electric charge, in N = 2 supersymmetric theories with SU (2) × U (1) N f gauge group. The quark numbers of the massless monopole at a nondegenerate singularity of QMS turn out to vanish in all cases. A puzzle related to CP invariant cases is solved. Generalization of our results to SU (N c ) × U (1) N f gauge theories is straightforward.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Such a connection has been confirmed in SU (2) theory with nonvanishing flavors, through the study of the flavor multiplet structure and fractional quark numbers of these monopoles [21], [22].…”
Section: Semiclassical Monopole Multiplets and Singularities Of Qmsmentioning
confidence: 71%
See 1 more Smart Citation
“…Such a connection has been confirmed in SU (2) theory with nonvanishing flavors, through the study of the flavor multiplet structure and fractional quark numbers of these monopoles [21], [22].…”
Section: Semiclassical Monopole Multiplets and Singularities Of Qmsmentioning
confidence: 71%
“…This can be easily deduced from the form of the hyperelleptic curve near the Chebyshev point of the m i = 0 theory. Writing the curve as 22) we note that near the Chebyshev point (the maximally degenerate point) n f /2 + 1 φ a 's must be "small" (i.e. vanishing in the zero mass limit) while the rest, being (perturbed) roots of the Chebyshev polynomial of the m i = 0 theory must all be finite and proportional to the N = 2 dynamical scale.…”
Section: Unequal Mass Perturbation At Chebyshev Pointsmentioning
confidence: 99%
“…One point touched on briefly in passing concerns the fractional fermion number, which appears as the phase of the CFIV index counting BPS states in 1+1D, and it is natural to ask whether it has a similar interpretation in the bulk. The natural point of contact is the fractional quark charge of dyonic states, given by 2π∆S i = Im(∂Z kl /∂m i ) for the i th flavor [40,41,42], which is analogous to the Witten effect shifting the electric charge [24], and indeed is equivalent at the baryonic root. For a given extremal point e k , we have the comparison,…”
Section: Discussionmentioning
confidence: 99%
“…Some of these couplings have a nice physical interpretation. In[17] it has been shown that Re(τ af ) is related to the physical baryon numbers of the BPS states by a generalized Witten effect. On the other hand, in the topological version of the N = 2 theory, the coupling τ 00 appears as a contact term for a family of operators[14,15,16].…”
mentioning
confidence: 99%